Essential oil constituents assessment and antioxidant profiles of Stevia rebaudiana Bertoni leaves from Malaysia - Mohd Zaki, Nur Izzati; Zaidan, Uswatun Hasanah; Abd Gani, Siti Salwa; Abu Bakar, Suhaili; Halmi, Mohd Izuan Effendi (Malaysian Society of Applied Biology, 2019)
Since the 15th century, essential oils (EO) were having a strong interest as therapeutic agents and recently EO has been widely used in pharmaceutical, cosmetic, food and agricultural industries. The previous study showed that EOs from Stevia rebaudiana Bertoni (SrB) possess high antioxidant, anti-inflammatory, and antimicrobial properties. In this study, the chemical constituents of EO from SrB leaves which grown in Selangor, Malaysia were obtained by ethanol Soxhlet extraction. Total polyphenolic content (TPC), total flavonoid content (TFC), and chemical composition using a gas chromatography-mass selective detector (GC-MSD) analyses of Stevia rebaudiana Bertoni essential oil (SrB EO) were carried out. The TPC and TFC of SrB EO were 14.44±0.63 mg gallic acid equivalent (GAE) /g sample extract and 32.19±1.38 mg quercetin equivalent (QE)/g sample extract, respectively. Based on GC-MSD analyses, one hundred peaks were obtained and 28 compounds were identified where lupeyl acetate occupied the highest percentage with 14.25% of the chemical constituents. The antioxidant activities of SrB EO were studied using 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2-azino-bis(3-ethylbenzothiazoline-6- sulphonic acid (ABTS), and ferric reducing antioxidant power (FRAP) assays. The IC50 of SrB EO using DPPH and ABTS were 71.36±1.57 µg/mL Trolox equivalent (TE) and 8.88×102±0.16 µg/mL TE, respectively while the FRAP activity was 9.55±0.26 mg/g TE. These results show the promising antioxidant properties of SrB EO.